Hydroxyurea as a first-line treatment of extramedullary hematopoiesis in patients with beta thalassemia: Four case reports. (January 2015) - Karimi, Mehran; Cohan, Nader; Pishdad, Parisa
Abstract : Objective and importance: Extramedullary hematopoiesis (EMH) is evidenced by erythropoietic masses, which occurs as a compensatory mechanism to overcome hypoxia during chronic anemia. EMH masses in spinal cord could lead to cord compression and neurological symptoms. Besides transfusion, radiotherapy, and surgery, hydroxyurea (HU) is also a treatment strategy in EMH. Clinical presentation: We described four cases of beta thalassemia with EMH who were treated with HU as a monotherapy. Intervention (and technique): HU therapy was done in all patients without any transfusion during therapy. Conclusion: HU is a good treatment option for patients with EMH and it could be a substitute for radiotherapy and invasive surgery or regular blood transfusion.